Is Job Loss Always Bad for Health? Evidence from National Health Screening - Hwang, Jisoo; Kim, Hyuncheol Bryant; Lee, Jungmin (The Review of Economics and Statistics, 2025)
We examine the effect of job displacement on mortality, hospitalization, biomarkers, and health behaviors in South Korea. We find that the impact on health differs between severe and less severe outcomes and also by gender. Men experience little impact on mortality and hospitalization except for an increase in suicide deaths, whereas their biomarkers and health behaviors improve. Women experience an increase in mortality and hospitalization due to cancer, but no significant effects on biomarkers or health behaviors. The study emphasizes the need to consider a comprehensive range of outcomes to accurately evaluate the effect of job loss on health.